APLIKASI THEORY OF PLANNED BEHAVIOUR : KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KOTA SURABAYA - DWI PANGESTIE, DHEA; DUDY SETYAWAN, MADE (Jurnal Akuntansi AKUNESA, 2019)
This purpose of this study was determine the effect of variables contained in the Theory of Planned Behaviour, namely attitudes, subjective norms, behavioural control, and intention of taxpayer compliance. The object under study is the land and building taxpayer in Surabaya. The sample was 138 Land and Building taxpayers. The study was conducted using questionnaire with data analysis Structural Equation Model (SEM) approach based on Partial Least Square (PLS) with the WarpPLS 3.0 application. The result show that attitudes, subjective norms, and behavioral control has a positive effect on intention. Intention and behavioural control has a positive effect on land and building tax compliance. Keywords: Attitudes; Subjective Norms; Behavior Control; Intention; Land and Building Taxpayer Compliance